2017
DOI: 10.1002/jcp.25931
|View full text |Cite
|
Sign up to set email alerts
|

Fasting up‐regulates ferroportin 1 expression via a Ghrelin/GHSR/MAPK signaling pathway

Abstract: The significant positive correlation between ghrelin and iron and hepcidin levels in the plasma of children with iron deficiency anemia prompted us to hypothesize that ghrelin may affect iron metabolism. Here, we investigated the effects of fasting or ghrelin on the expression of hepcidin, ferroportin 1 (Fpn1), transferrin receptor 1 (TfR1), ferritin light chain (Ft-L) proteins, and ghrelin, and also hormone secretagogue receptor 1 alpha (GHSR1α) and ghrelin O-acyltransferase (GOAT) mRNAs in the spleen and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…It has been confirmed that the proliferative role of ghrelin is related to the activation of its downstream MAPK signaling cascade in multiple types of cells [43,44]. Our previous investigation also suggested that Fpn1 expression increased after ERK phosphorylation in the spleen/macrophages [25]. To determine whether ghrelin also increases the expression of Fpn1 through the GHSR1a/MAPK signaling pathway in cultured hepatocytes, we explored the role of ghrelin in ERK phosphorylation in the presence or absence of a MAPK signaling pathway inhibitor (U0126).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It has been confirmed that the proliferative role of ghrelin is related to the activation of its downstream MAPK signaling cascade in multiple types of cells [43,44]. Our previous investigation also suggested that Fpn1 expression increased after ERK phosphorylation in the spleen/macrophages [25]. To determine whether ghrelin also increases the expression of Fpn1 through the GHSR1a/MAPK signaling pathway in cultured hepatocytes, we explored the role of ghrelin in ERK phosphorylation in the presence or absence of a MAPK signaling pathway inhibitor (U0126).…”
Section: Discussionsupporting
confidence: 53%
“…An investigation by Dogan et al suggested that while children suffering from IDA showed lower levels of serum hepcidin and ghrelin than healthy children, iron treatment significantly elevated the hepcidin and ghrelin levels in the serum of IDA children [24]. In our previous study, a statistically significant negative correlation was also found between iron levels and ghrelin in the serum [25]. Based on these findings, we hypothesized that ghrelin may modulate the balance of iron homeostasis under physiological conditions.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Ghrelin concentrations are primarily regulated by food intake. Hence, ghrelin levels increase during fasting (in line with increased hunger) and are generally lower in individuals with higher body weights compared with lean individuals, suggesting a role for ghrelin in the regulation of body weight [49].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was performed as described in our previous work (Luo et al, 2018 ). Cells were fixed in 4% paraformaldehyde for 30 min followed by three washes in 0.01 M PBS.…”
Section: Methodsmentioning
confidence: 99%